Crowding out or no crowding out?: a self-determination theory approach to health worker motivation in performance-based financing - Lohmann, Julia; Houlfort, Nathalie; De Allegri, Manuela (Social science & medicine, 2016)
Performance-based financing (PBF) is a common health system reform approach in low and middle income countries at present. Although increasing evidence on the effectiveness of PBF and knowledge of principles of good design are available, research is still lacking in regards to other aspects. Among these are a yet limited understanding of the complex role of health worker motivation in PBF and of potential side effects, for instance on intrinsic motivation. Our article aims to support meaningful future research by advancing the theoretical discussion around health worker motivation and PBF. We argue that an in-depth understanding of the motivational mechanisms and consequences of PBF at health worker level are of high practical relevance and should be at the heart of the PBF research agenda, and that predominant unidimensional conceptualizations of health worker motivation and descriptive rather than explanatory research approaches are insufficient to fully understand whether, how, and why PBF schemes alter health workers' motivational structures, mindsets, affect, and behavior. We introduce and apply Self-Determination Theory to the context of PBF as a valuable theoretical framework for future empirical exploration. From this, we conclude that PBF interventions are unlikely to have a generally adverse effect on intrinsic motivation as feared by parts of the PBF community. Rather, we posit that PBF can have positive and negative effects on both intrinsic and extrinsic motivation, to varying degrees depending on the specific design, implementation, and results of a particular intervention and on health workers' perceptions and evaluations of it.
Gesehen am 14.05.2020